2014 IEEE 26th International Symposium on Power Semiconductor Devices &Amp; IC's (ISPSD) 2014
DOI: 10.1109/ispsd.2014.6855978
|View full text |Cite
|
Sign up to set email alerts
|

Short-circuit robustness of SiC Power MOSFETs: Experimental analysis

Abstract: This paper proposes a thorough experimental characterization of the performance of commercially available SiC Power MOSFETs under short-circuit conditions. The purpose is to assess and understand the degradation process and the failure mechanisms that limit device reliability to identify optimal routes for subsequent technology development. This paper complements electro-thermal functional tests with structural characterization offering deeper insight into device technology related aspects.I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…These effects were already reported in [33], and they are 214 present in different devices as well, upheld by test results 215 (Figs. 6 and 7).…”
supporting
confidence: 52%
“…These effects were already reported in [33], and they are 214 present in different devices as well, upheld by test results 215 (Figs. 6 and 7).…”
supporting
confidence: 52%
“…Two main results as reported in [6] are worth to be recalled. First, at the end of the SC pulse, a change in slope of drain current appears.…”
Section: Resultsmentioning
confidence: 88%
“…This paper is focused on the interpretation of degradation and failure mechanism of SiC power MOSFETs operating in SC conditions, to extend our previous work [6], employing experimental results and by means of calibrated electrothermal (ET) TCAD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In these conditions the device is able to withstand well in excess of 10 s, the longest pulse before failure being 160 s: the subsequent pulse, with a width of 161 s, led to device catastrophic failure. To assist the interpretation of the failure mechanism, advantage was taken of structural characterisation of the devices, in the form of fast transient infrared thermography of the active surface [18]. Fig.…”
Section: Single-pulse Short-circuit Robustnessmentioning
confidence: 99%
“…The investigations in [18] and in [22] have shown that as a result of both, commercially available SiC power MOSFETs do exhibit a pronounced variation of some of their electro-thermal parameters. If the energies involved in the stress process are sufficiently lower than the maximum values the devices can withstand, then aging does not imply loss of functionality, but rather decreased performance only.…”
Section: Aging After Repetitive Stressmentioning
confidence: 99%